The 2008 Tibet Riots: Competing perspectives, divided group protests and divergent media narratives - Li, C.; Montgomery, Lucy (Peter Lang, 2011)
This chapter explores the contending interpretations of riots that took place in Lhasa, Tibet in the lead-up to the Beijing Olympics in 2008 as they were presented by the British elite television news and online newspapers and the Xinhua News Agency and China Central Television. The riots took place in the context of an international campaign by pro-independence activists intended to capitalise on international media interest in China associated with the Olympics. News coverage of the riots itself became the catalyst of trans-national protests against ‘western media bias’, in which Chinese students studying overseas played a key role. In addition to Chinese and British media coverage of the protests, the chapter draws on focus-group interviews with forty one Chinese students and forty three British students, all of whom were studying at British universities and living in the UK when the Tibet riots occurred.